A randomized phase III study of the docetaxel/carboplatin combination versus docetaxel single-agent as second line treatment for patients with advanced/metastatic Non-Small Cell Lung Cancer - Pavlakou Georgia; Kentepozidis Nikolaos; Syrigos Kostas; Varthalitis Ioannis; Agelidou Athina; Agelaki Sophia; Pallis Athanasios G; Kotsakis Athanasios; Kontopodis Emmanouel; Georgoulias Vassilis (BMC Cancer, 2010)
Abstract Background To compare the activity and toxicity of docetaxel/carboplatin (DC) doublet vs single agent docetaxel (D) as second-line treatment in patients with advanced non-small cell lung cancer (NSCLC). Methods Patients pre-treated with front-line platinum-free regimens, were randomized to receive either docetaxel/carboplatin (DC), (docetaxel 50 mg/m2; carboplatin AUC4; both drugs administered on days 1 and 15) or docetaxel single-agent (D), (docetaxel 50 mg/m2 on days 1 and 15). Results Response rate was similar between the two arms (DC vs D: 10.4% vs 7.7%; p = 0.764). After a median follow-up time of 28.0 months for DC arm and 34.5 months for D arm, progression free survival (PFS) was significantly higher in the DC arm (DC vs D:3.33 months vs 2.60 months; p-value = 0.012), while no significant difference was observed in terms of overall survival (OS) (DC vs D: 10.3 months vs 7.70 months; p-value = 0.550). Chemotherapy was well-tolerated and grade III/IV toxicities were relatively infrequent. No toxic deaths were observed. Conclusions This study has not achieved its primary objective of significant OS prolongation with docetaxel/carboplatin combination over single-agent docetaxel in patients who had not received front-line docetaxel; however, the docetaxel/carboplatin combination was associated with a significant clinical benefit in terms of PFS.